Synergistic influence of the capture effect of western flower thrips (Frankliniella occidentalis) induced by proportional yellow-green light in the greenhouse - Liu, Qihang; Wang, Xinfa; Zhao, Mingfu; Liu, Tao (International Journal of Agricultural and Biological Engineering, 2023)
To clarify the influence of yellow, green, and proportional yellow-green light on the capture effect, western flower thrips, Frankliniella occidentalis (Pergande), were captured using different self-made light sources in a greenhouse. The bio-activity capture effect of thrips was regulated by light and analyzed to determine the reasons for the changes in their capture by light. The results showed that the thrips’ capture effect induced by different light sources with the same brightness was positively correlated with night temperature. When the average night temperature was 27°C (19:00-21:30), the capture effect was optimal, indicating that the coupling effect of light temperature can regulate the capture effect of thrips. Green light intensified and yellow light inhibited the visual trend sensitivity of thrips to yellow-green light of differing proportions. The capture effect trapped by a green-yellow light ratio of 4:1 was optimal (1088.00 individuals in night time), while that of yellow light was the worst (456.67 individuals/night), thus, indicating that visual trend sensitivity of thrips to green light was higher than that of yellow light. Such differences originated from the differences in the photoelectric thermal conversion effect of spectral optical properties, and the spectral photo-thermal effect was the main reason that thrips produced a light-trapped behavior. Night light enhanced the sensitivity of thrips’ responses to a white adhesive board during the daytime, and the effect of yellow light intensity was the strongest (1563.00 individuals in the daytime), while that of green light was the weakest (75.33 individuals in the day time). Additionally, yellow light intensified while green light inhibited the regulatory effect of different proportions of yellow-green light on the bio-activity of thrips. However, the capture effect of day and night corresponding to 4:1 green-yellow light was the best (2019.67 individuals in day and night). The function of the photo-thermal effect on the capture effect of thrips was affected by the decrease in night temperature, but the photo-electro-thermal effects of night light intensified the bio-activity of thrips in the daytime and enhanced their color sensitivity. The results provide a theoretical basis for the development of pest light induction equipment. Keywords: western flower thrips, proportional yellow-green light, synergistic influence effect, capture effect DOI: 10.25165/j.ijabe.20231601.7562 Citation: Liu Q H, Wang X F, Zhao M F, Liu T. Synergistic influence of the capture effect of western flower thrips (Frankliniella occidentalis) induced by proportional yellow-green light in the greenhouse. Int J Agric & Biol Eng, 2023; 16(1): 88–94.